CASPASE 9 GENE EXPRESSION AND CASPASE 9 PROTEIN IN CHRONIC MYELOID LEUKEMIA IN IRAQ - K., Abdullah W.; A., Maha F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The following study was carried out to investigate gene expressions of the CASPASE 9 gene and CASPASE 9 protein with the development of chronic myeloid leukemia (CML) in Iraq. The differences in the expression of this gene between patients and healthy controls were included. The correlation of age and gender with CML occurrence comparing with controls was studied. Results showed significant increases in the mean of gene expression level (ΔCt) of patient groups compared to the corresponding ΔCt means in control group, also the gene expression folding (2-∆∆Ct) of  CASPASE 9  gene  reflect significant differences in the expression showed the highest level in CML patients which reached to (16.19), the level of CASPASE 9 protein was (1.025 ng/ml) in patients with CML compared to control groups with significant differences.  On the other hand no significant differences were exhibited according to age and gender between CML patients and control, this result suggest that CML can affect all ages and occur in both male and females.